Motivated reasoning, information avoidance, and default bias - Katharina Momsen; Sebastian O. Schneider (Max Planck Institute for Research on Collective Goods, 2022)
We investigate whether the presence of a default interacts with the willingness of decision-makers to gather, process and consider information. In an online experiment, where about 2,300 participants choose between two compiled charity donation options worth 100, we vary the availability of information and the presence of a default. Information avoidance, when possible, increases default effects considerably, manifesting a hitherto undocumented channel of the default bias. Moreover, we show that defaults trigger motivated reasoning: In the presence of a default - even if self-selected-, participants consider new information to a lower degree than without a preselected option.
hdl:21.11116/0000-000A-3221-8
Keywords: C90; D64; D83; D91; 330; Motivated reasoning; information avoidance; defaults; statusquo; charitable giving; experiment